2021
DOI: 10.1161/atvbaha.121.315957
|View full text |Cite
|
Sign up to set email alerts
|

Nrg1β Released in Remote Ischemic Preconditioning Improves Myocardial Perfusion and Decreases Ischemia/Reperfusion Injury via ErbB2-Mediated Rescue of Endothelial Nitric Oxide Synthase and Abrogation of Trx2 Autophagy

Abstract: Objective: Remote ischemic preconditioning (RIPC) is an intervention process where the application of multiple cycles of short ischemia/reperfusion (I/R) in a remote vascular bed provides protection against I/R injury. However, the identity of the specific RIPC factor and the mechanism by which RIPC alleviates I/R injury remains unclear. Here, we have investigated the identity and the mechanism by which the RIPC factor provides protection. Approach and ResultS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Myocardial ECs upregulate NRG1 release during ischemic injury ( Fukazawa et al, 2003 ; Hedhli et al, 2011 ). The receptor for NRG1, ErbB2, was found to be expressed only in ECs, but not in cardiomyocytes from adult mouse hearts ( Kundumani-Sridharan et al, 2021 ). NRG1-ErbB2 can regulate angiogenesis not only through the activation of HIF-1α (hypoxia-inducible factor-1α) via the PI3K/AKT/mTOR pathway ( Karar and Maity, 2011 ), but also through paracrine up-regulation of VEGF to induce angiogenesis ( Xu et al, 2010 ).…”
Section: Nrg1 With Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial ECs upregulate NRG1 release during ischemic injury ( Fukazawa et al, 2003 ; Hedhli et al, 2011 ). The receptor for NRG1, ErbB2, was found to be expressed only in ECs, but not in cardiomyocytes from adult mouse hearts ( Kundumani-Sridharan et al, 2021 ). NRG1-ErbB2 can regulate angiogenesis not only through the activation of HIF-1α (hypoxia-inducible factor-1α) via the PI3K/AKT/mTOR pathway ( Karar and Maity, 2011 ), but also through paracrine up-regulation of VEGF to induce angiogenesis ( Xu et al, 2010 ).…”
Section: Nrg1 With Cardiovascular Diseasesmentioning
confidence: 99%
“…NRG1 administration activates multiple signaling pathways to stimulate reentry and division of the adult cardiomyocyte cycle ( D'Uva et al, 2015 ; Lin et al, 2015 ) and induce myocardial regeneration. Exogenous administration of NRG1 promotes the expression of genes related to the type of work ( Zhu et al, 2010 ) and induces cardiomyocyte differentiation into cardiac conduction system cells ( Rentschler et al, 2002 ), promotes stem cell differentiation into working-type cardiomyocytes ( Suk Kim et al, 2003 ), and improves cardiac tissue function after pathological injury ( Mendes-Ferreira et al, 2016 ; Kundumani-Sridharan et al, 2021 ; Sun et al, 2021 ), and are the most promising molecules for promoting cardiac repair under experimental conditions and clinical trials ( Gao et al, 2010 ; Jabbour et al, 2011a ; Polizzotti et al, 2015 ). Herein, this article summarizes the molecular mechanisms of NRG1 and its recent findings in cardiovascular biology, clinical applications in cardiovascular repair, and proposed areas of future research.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin was reported to play a beneficial role in CMECs against I/R injury through directly suppressing autophagy via the AMPK/mTOR pathway [123] or by inhibiting the mitophagy-mediated cell death via the dynamin-related protein 1 (Drp1)-voltage-dependent anion channel 1 (VDAC1)-hexokinase 2 (HK2)-mitochondrial permeability transition pore (mPTP)-PINK1/Parkin axis in an AMPKα-dependent manner [124]. Furthermore, neuregulin-1β (Nrg1β) protected the cardiac ECs against I/R injury by preventing ATG5-required autophagy-induced Trx2 (thioredoxin) degradation and rescuing eNOS function via upregulating the Erb-B2 receptor tyrosine kinase 2 (ErbB2) [125]. In addition, Diao et al found that a long noncoding RNA (LncRNA) UCA1 transferred from human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-ex) protected the CMECs against H/R injury by inhibiting autophagy via damaging the miR-143mediated degradation of Bcl-2 [126].…”
Section: Coronary Endothelial Autophagy In Obstructive Cad (Stable Ca...mentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11132081/s1, Table S1: Mechanistic studies implicating endothelial autophagy or mitophagy in cardiovascular diseases [93,105,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][130][131][132][133][149][150][151][152][153][154][155][156][157][158][159][160][166][167][168][169][170]181,[184][185][186][187]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Accumulating evidence has revealed that the interaction between cardiomyocytes and vasculature is essential for the maintenance of cardiac homeostasis. Cardiomyocytes produce angioprotective cytokines/growth factors, such as vascular endothelial growth factor (VEGF), and maintain vascular function, whereas endothelial cells prevent cardiomyocyte death by secreting cardioprotective cytokines/growth factors including neuregulin (Hemanthakumar & Kivelä, 2020 ; Kivelä et al, 2019 ; Kundumani‐Sridharan et al, 2021 ; Räsänen et al, 2021 ; Segers et al, 2018 ; Shen & Abe, 2021 ).…”
Section: Introductionmentioning
confidence: 99%